Zebrafish as a model of mammalian cardiac function: Optically mapping the interplay of temperature and rate on voltage and calcium dynamics. (October 2018) - Rayani, Kaveh; Lin, Eric; Craig, Calvin; Lamothe, Marcel; Shafaattalab, Sanam; Gunawan, Marvin; Li, Alison Yueh; Hove-Madsen, Leif; Tibbits, Glen F.
Abstract: The zebrafish ( Danio rerio ) heart is a viable model of mammalian cardiovascular function due to similarities in heart rate, ultrastructure, and action potential morphology. Zebrafish are able to tolerate a wide range of naturally occurring temperatures through altering chronotropic and inotropic properties of the heart. Optical mapping of cannulated zebrafish hearts can be used to assess the effect of temperature on excitation-contraction (EC) coupling and to explore the mechanisms underlying voltage (Vm ) and calcium (Ca 2+ ) transients. Applicability of zebrafish as a model of mammalian cardiac physiology should be understood in the context of numerous subtle differences in structure, ion channel expression, and Ca 2+ handling. In contrast to mammalian systems, Ca 2+ release from the sarcoplasmic reticulum (SR) plays a relatively small role in activating the contractile apparatus in teleosts, which may contribute to differences in restitution. The contractile function of the zebrafish heart is closely tied to extracellular Ca 2+ which enters cardiomyocytes through L-type Ca 2+ channel (LTCC), T-type Ca 2+ channel (TTCC), and the sodium-calcium exchanger (NCX). Novel data found that despite large temperature effects on heart rate, Vm, and Ca 2+ durations, the relationship between Vm and Ca 2+ signals was only minimally altered in the face of acute temperature change. This suggests that zebrafish Vm and Ca 2+ kinetics are largely rate-independent. In comparison to mammalian systems, zebrafish Ca 2+ cycling is inherently more dependent on transsarcolemmal Ca 2+ transport and less reliant on SR Ca 2+ release. However, the compensatory actions of various components of the Ca 2+ cycling machinery of the zebrafish cardiomyocytes, allow for maintenance of EC coupling over a wide range of environmental temperatures.